Flexibility and security over the life course - Muffels, Ruud.; Chung, Heejung; Fouarge, Didier; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
This report presents the findings of a research project carried out in 2006 and 2007 by the European Foundation for the Improvement of Living and Working Conditions (hereafter referred to as the Foundation). This project aimed to examine the long-term effects of the ongoing trend towards greater flexibility in employment contracts and working time in the European labour market. The research considered developments at national (macro) level, company (meso) level and worker (micro) level. The main research concerns are, first, what this 'flexibilisation' trend means for workers in meeting their needs for reconciling work and private life and for improving their work-life balance. At the same time, the study explores the implications for employers in meeting their flexibility needs over the company's life cycle. In the context of such flexibility, income and employment security in society should be safeguarded and labour market segmentation avoided.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Flextime -- European Union countries; Job security -- Europe; Quality of work life -- European Union countries; Electronic books